Evaluation of nandrolone and ractopamine in the urine of veal calves: liquid chromatography‐tandem mass spectrometry approach. Issue 4 (22nd July 2016) - Chiesa, L.; Panseri, S.; Cannizzo, F.T.; Biolatti, B.; Divari, S.; Benevelli, R.; Arioli, F.; Pavlovic, R.
Abstract : Under European legislation, the use of growth promoters is forbidden in food‐producing livestock. The application of unofficial protocols with diverse combinations of veterinary drugs, administered in very low concentrations, hinders reliable detection and subsequent operative prevention. It was observed that nandrolone (anabolic steroid) and ractopamine (β‐adrenergic agonist) are occasionally administered to animals, but little is known about their synergic action when they are administered together. Two specific analytical methods based on liquid chromatography‐tandem mass spectrometry have been developed, both of which include hydrolysis of the corresponding conjugates. For the nandrolone method, solid‐phase extraction was necessary for the complete elimination of the interferences, while employment of the Quantitation Enhanced Data‐Dependent scan mode during MS acquisition of ractopamine enabled the utilization of simple liquid‐liquid extraction. The nandrolone method was linear in the range of 0.5–25 ng/mL, while the ractopamine calibration curve was constructed from 0.5 to 1000 ng/mL. The corresponding coefficients of correlations were >0.9907. The lower limit of quantification for both methods was 0.5 ng/mL, followed by overall recoveries >81%. Precisions expressed as relative standard deviations were <17%, while matrix effects were minimal. Urine samples taken at the slaughterhouse from veal calves enrolled in an experimental treatment consisting of intramuscular administration of β‐nandrolone‐phenylpropionate accompanied with a ractopamine‐enriched diet were analysed. Those methods might be useful for studying the elimination patterns of the administered compounds along with characterization of the main metabolic pathways. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Nandrolone (anabolic steroid) and ractopamine (β‐adrenergic agonist) are used quite frequently in food‐producing livestock, but little is known about their synergic action when they are administered together. The objective of this study was to determine levels after experimental treatment of bovines with both of the above‐mentioned drugs. For this purpose two specific analytical methods based on liquid chromatography‐tandem mass spectrometry were developed.